ECO-FRIENDLY TRANSFORMATION IN BEAUTY SALONS: OPPORTUNITIES AND HURDLES IN GREEN ENTREPRENEURSHIP-A REVIEW - Abisha A; C.L. Jeba Melvin (Utilitas Mathematica, 2025)
The beauty salon industry is crucial to the economy but is under pressure to implement sustainable practices in response to environmental issues. The present study examines the problems and opportunities associated with green entrepreneurship, emphasizing challenges such as elevated costs, restricted access to eco-friendly materials, knowledge deficiencies, and reluctance to change, particularly within small salons. Nonetheless, the pursuit of sustainability yields advantages such as differentiation in the market, loyalty amongst customers, and cost savings through enhanced efficiency and waste minimization. The rising consumer demand for environmentally sustainable services, along with governmental incentives, bolsters this transformation. The study underscores a lack of industry-specific strategies and regional insights. By using biodegradable products, optimizing resources, and adopting sustainable branding, salons can align with global sustainability goals and enhance their competitiveness. Collaboration among policymakers, suppliers, and salon owners is crucial to create a supportive ecosystem. Overall, despite existing challenges, pursuing green entrepreneurship is essential for salons aiming for environmental responsibility and business growth.